Analysis of Bit Error Rate Performance and Atmospheric Attenuation Coefficient of Free Space Optical(FSO) Link - Harjeevan Singh ,Nittin Mittal ,Harbinder Singh (International Journal of Advanced Science and Technology, 2020)
FSOC involves the sending of signal using laser through free space.The most basicmodulationtechnique used for Free Space Optical link is OOK.The Simplicity of this technique makes it a goodoption for FSO link.This paper investigates the system performance under OOK and PPM modulationtechniques.The BER of FSO link using OOK and 8-PPM has been analyzed under atmosphericturbulence.Furthermore, the effect of rain and snow has been investigated and the attenuationcoefficient for free space optical link has been studied for different rain rate and snow rate